2006
DOI: 10.1194/jlr.m500542-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Structures and biological activities of novel phosphatidylethanolamine lipids of Porphyromonas gingivalis

Abstract: The Gram-negative periodontal pathogen Porphyromonas gingivalis synthesizes several classes of novel phosphorylated complex lipids, including the recently characterized phosphorylated dihydroceramides. These sphingolipids promote the interleukin-1 (IL-1)-mediated secretion of inflammatory mediators from fibroblasts, including prostaglandin E 2 and 6-keto prostaglandin F 2a , and alter gingival fibroblast morphology in culture. This report demonstrates that one additional class of phosphorylated complex lipids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
(36 reference statements)
0
37
0
Order By: Relevance
“…gingivalis infection enhanced the secretion of the cytokines IL-1b, IL-6, IL-12 (p70), TNF-a, G-CSF, and GM-CSF, in addition to the chemokines eotaxin, MCP-1, MIP-1a, and MIP-b from macrophages, reflecting a proinflammatory response. These cytokines and chemokines are reported to act as proinflammatory mediators, induce monocytes to migrate from the bloodstream into gingival tissue, and act synergistically to further stimulate proinflammatory cytokine production (22,25,31,33,50,54,100). In addition, IL-10, which is produced primarily by macrophages, was detected among the vast array of cytokines induced by P. gingivalis infection.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…gingivalis infection enhanced the secretion of the cytokines IL-1b, IL-6, IL-12 (p70), TNF-a, G-CSF, and GM-CSF, in addition to the chemokines eotaxin, MCP-1, MIP-1a, and MIP-b from macrophages, reflecting a proinflammatory response. These cytokines and chemokines are reported to act as proinflammatory mediators, induce monocytes to migrate from the bloodstream into gingival tissue, and act synergistically to further stimulate proinflammatory cytokine production (22,25,31,33,50,54,100). In addition, IL-10, which is produced primarily by macrophages, was detected among the vast array of cytokines induced by P. gingivalis infection.…”
Section: Figurementioning
confidence: 99%
“…In addition to P. gingivalis proteins and LPS penetrating gingival tissue, P. gingivalis phosphorylated dihydoceramide lipids have been isolated from gingival tissue and subgingival plaque of chronic periodontitis patients (52)(53)(54). Whole P. gingivalis cells and certain components, including the RgpA-Kgp complexes and lipids, induce secretion of a number of proinflammatory cytokines from epithelial and fibroblast cells in vitro, such as IL-1, IL-6, IL-8, PGE 2 , macrophage chemoattractant protein (MCP)-1a, and ICAM-1 (50,54,55). The elevation in levels of the proinflammatory cytokines IL-1, IL-6, IL-8, IL-12, and TNF-a is commonly found in diseased gingival tissue of chronic periodontitis (19)(20)(21)30).…”
mentioning
confidence: 99%
“…Having previously demonstrated that bacterial phosphorylated dihydroceramides promote inflammatory responses in human fibroblasts in vitro, 4,5 we wanted to characterize the functional effects of these lipids in autoimmunity and used the murine model of multiple sclerosis, EAE. EAE was induced in female C57BL/6 mice and these mice were also injected intraperitoneally (i.p.)…”
Section: P Gingivalis Total Phosphorylated Dihydroceramide Lipids Amentioning
confidence: 99%
“…We have previously characterized uniquely structured, non-lipopolysaccharide (LPS), phosphorylated sphingolipid classes, termed phosphorylated dihydroceramides, produced by this organism. We reported that these lipids promote inflammatory responses in human fibroblasts in vitro, 4,5 and in recent preliminary studies (F.C. Nichols, unpublished) we have successfully recovered these lipids from surgically removed human carotid atheroma.…”
mentioning
confidence: 99%
See 1 more Smart Citation